Global Investigation of Immune Repertoire Suggests Kawasaki Disease Has Infectious Cause - Huang, Ying-Hsien; Huang, Fu-Chen; Huang, Lien-Hung; Li, Sung-Chou; Kuo, Ho-Chang; Pan, Cheng-Tsung; Lin, Yeong-Shin (Circulation Journal, 2019)
Background:Kawasaki disease (KD) severely threatens young children’s health worldwide. The pathogenic mechanism of KD has not yet been solved, so there is still debate over whether KD is an infectious disease or an autoimmune disease.Methods and Results:To solve this problem, an immune repertoire analysis of KD was conducted. We collected blood cell RNA samples and prepared them into amplicons with iRepertoire kits. The amplicons were sequenced and analyzed with the iRepertoire pipeline. We first identified KD-specific VJ and VDJ forms that had the potential to serve as biomarkers of KD. In addition, the KD-specific VDJ forms were contributed mostly by immunoglobulin G. The D50 value analysis showed that B-cell diversity in KD is decreased, suggesting unique immunoglobulins are produced in KD. Moreover, V, D and J segment usage in IgA, IgG and IgM was consistent with previous KD studies. Further comparison showed no difference in CDR3 peptide length between KD and fever controls (subjects with fever but not diagnosed as KD), indicting KD had B-cell selection phenomenon that has a non-autoimmune pattern. The comparison of amino acid usage of the CDR3 region demonstrated a preference for hydrophilic amino acids in KD.Conclusions:The results of D50 value, VDJ usage and CDR3 peptide length analyses suggested the characteristics of infectious disease for KD.